Chemical Composition and Mechanism of Vibriocidal Action of Essential Oil from Resin of Protium heptaphyllum. (23rd October 2019) - Mendes, Josiane Lima; de Araújo, Thiago Ferreira; Geraldo de Carvalho, Mário; Aragão Catunda Júnior, Francisco Eduardo; Albuquerque Costa, Renata
Abstract : Protium heptaphyllum is a plant widely distributed in Brazilian ecosystems that produce a resin which has pharmacological activities. In this study, the chemical composition, antimicrobial and antibiofilm activity, and the possible mechanism of action against the bacterium V. parahaemolyticus of essential oil from P. heptaphyllum (EOPH) were investigated. Twenty-two components were detected in EOPH, and β -phellandrene (60.68%) had the majority. The inhibition halo, MIC, and MBC values were 11 mm, 2 mg/mL, and 8 mg/mL, respectively. Biofilm biomass inhibition and biomass reduction of the preformed biofilm were detected at 4 mg/mL EOPH concentration. The assays of cell constituent release and membrane permeability indicated that EOPH may disrupt the cell membrane, leading to leakage of intracellular constituent as reducing sugars and materials with an absorbance of 260 nm.